2017
DOI: 10.3892/ol.2017.6558
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-154 inhibits the growth and metastasis of gastric cancer cells by directly targeting MTDH

Abstract: Abstract. MicroRNAs (miRNAs) are a group of non-protein-coding, highly conserved single-stranded RNA molecules. The abnormal expression of miRNAs has been demonstrated to have an important function in the carcinogenesis and progression of gastric cancer. microRNA-154 (miR-154) has been reported to be downregulated in non-small cell lung, colorectal and prostate cancer. However, the expression and roles of miR-154 in gastric cancer remain to be established. The present study measured the expression levels of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…32 They are involved in various processes such as angiogenesis, 33 cell growth, 34 and movement. 36 miR-744 can inhibit GC cell proliferation and invasion through targeting neurotrophic factor. 10,11 miR-154 is able to repress GC cell development by inhibiting MTDH.…”
Section: Discussionmentioning
confidence: 99%
“…32 They are involved in various processes such as angiogenesis, 33 cell growth, 34 and movement. 36 miR-744 can inhibit GC cell proliferation and invasion through targeting neurotrophic factor. 10,11 miR-154 is able to repress GC cell development by inhibiting MTDH.…”
Section: Discussionmentioning
confidence: 99%
“…As miRNAs have been observed to regulate the proliferation, migration, invasion and other biological processes, a close association between miRNA expression and tumor progression has been reported (19). For instance, Qiao et al (20) reported that miR-154 inhibited the growth and metastasis of gastric cancer cells by directly targeting metadherin (20). Cao et al (17) revealed that miR-552 promoted tumor cell proliferation and migration by directly targeting dachshund family transcription factor 1 via the Wnt/β-catenin signaling pathway in colorectal cancer (17).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, reduced levels of miR-154 levels in colorectal cancer tissues compared with non-cancerous tissues has been reported and this low expression has been shown to be significantly correlated with aggressive clinicopathological characteristics such as large tumor size, positive lymph node metastasis, and advanced clinical stage (27). Low expression of miR-154 and its association with cell proliferation, migration and invasion has also been described in prostate cancer (28). miR-154 may also function as a tumor suppressor in non-small cell lung cancer (NSCLC) by binding to B-cell-specific Moloney murine leukemia virus insertion site 1 (BMI-1) (29).…”
Section: Luciferase Reporter Assay Verifying the Predicted Interactiomentioning
confidence: 95%